STUDY OF THE EXPERIENCE OF FOREIGN COUNTRIES IN THE ESTABLISHMENT OF FREE TOURIST ECONOMIC ZONES AND ANALYSIS OF THE SITUATION IN UZBEKISTAN - Asadova Aziza Olimjonovna; Muhammadiyeva Nodira Xusanovna (Research Parks Publishers, 2020)
This scientific article describes the free tourist economic zones, the purpose of their establishment, the situation in China and Russia, their analysis, existing problems, and opportunities. In particular, the advice was given on the existing opportunities in Uzbekistan, the potential of tourist resources, the state of the established free tourist zone